2021
DOI: 10.3390/jcm10112397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Feasibility and Effectiveness of Placement of Fully Covered Self-Expandable Metallic Stents via Various Insertion Routes for Benign Biliary Strictures

Abstract: Background and aims: The goals of the management of benign biliary stricture (BBS) are to relieve symptoms and resolve short-/long-term stricture. We performed fully covered self-expandable metallic stent (hereafter, FCSEMS) placement for BBS using various methods and investigated the treatment outcomes and adverse events (AEs). Methods: We retrospectively studied patients who underwent FCSEMS placement for refractory BBS through various approaches between January 2017 and February 2020. FCSEMS were placed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…An alternative approach to treating BBS involves the insertion of a removable FC-SEMS through a PTBD tract. In this method, the stent with a distal string is inserted in the conventional direction, and the string is fixed to the skin[ 9 ]. This carries a risk of peripheral stent migration along the string, infection through the string tract, and additional PTCS for stent removal[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to treating BBS involves the insertion of a removable FC-SEMS through a PTBD tract. In this method, the stent with a distal string is inserted in the conventional direction, and the string is fixed to the skin[ 9 ]. This carries a risk of peripheral stent migration along the string, infection through the string tract, and additional PTCS for stent removal[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Petersen et al [ 12 ] reported that moderate luminal narrowing (50%–60%) was observed at 5–6 months and one stent was occluded at 9 months. Tomishima et al [ 26 ] reported that stent fracture occurred in two cases (7.7%) in which the retrievable covered stents were placed for more than 6 months. According to these previous studies and our outcomes, leaving covered stents in situ for 6 months seems to be acceptable for benign biliary diseases in terms of stent durability and safety, although there is anecdotal evidence that some stents remain intact for a significantly longer period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stent migration can be prevented by changing the stent design through the addition of an anchoring flap 26 . Tomishima et al 27 reported that stent fracture occurred in 7.7% (2/26) after placement of CSEMS for benign biliary stricture. Although there have been no studies on the fracture rate of biodegradable biliary stents, in a previous human study using PDO stents 28 , 25% of patients developed mild cholangitis during stent indwelling.…”
Section: Discussionmentioning
confidence: 99%